(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
As the world awaits for a Covid-19 vaccine, the number of Covid-19 positive patients continues to increase unabated globally. Beyond social distancing, it is now a widely adopted practice for countries easing lock-down measures to deploy mass testing on its population. To support this mass testing during a period of supply chain disruption, we describe the successful development of a novel, cost-effective and manufacturable 3D printed nasopharyngeal swab for the detection of SARS-COV-2 virus. As a digital technology, 3D printing enables the fabrication of a product based on a digital design without going through the traditional mold fabrication and tooling qualification, resulting in rapid product development and validation cycles. The clinical efficacy of the swab design was compared to an industry standard swab, carried out in a case-controlled study of patients diagnosed with COVID-19 against control patients who had tested negative for SARS-CoV-2. Compared to the standard Copan FLOQswab, the 3D printed swab displayed excellent correlation of RT-PCR cycle threshold values on paired clinical testing, as well as excellent true positive and true negative agreements based on Cohen’s kappa.